A study on the debris flow-induced impact force on check dam with- and without-entrainment - Lee, Kwangwoo (2021)
The magnitude of debris-flow impact force with soil layer entrainment was analyzed using a coupled Eulerian-Lagrangian (CEL) technique in ABAQUS. To consider the entrainment of the soil layer, the shear strength of the soil layer was changed from a solid-state to a fluid state according to the deviatoric plastic strain. The applicability of the coupled Eulerian-Lagrangian (CEL) method to the analysis of debris flows with impact force on check dams was verified by comparing the analysis with laboratory tests. The result was clearly show that the analysis is in good agreement with the laboratory data. In addition, the analyses with entrainment and without entrainment were conducted to analyze the effect of the entrainment on the impact force. As a result, the impact force of the debris flows considering the entrainment process was more extensive than it was without entrainment. This rigorous Finite Element (FE) analysis method can specify the potential influence of debris flows, and it can estimate the dynamic impact force on check dams.